2015
DOI: 10.2151/jmsj.2015-050
|View full text |Cite
|
Sign up to set email alerts
|

Role of Maritime Continent Convection during the Preconditioning Stage of the Madden-Julian Oscillation Observed in CINDY2011/DYNAMO

Abstract: We investigated the role of Sumatra Island convection over the maritime continent during the preconditioning stage of the Madden-Julian Oscillation (MJO) using intensive observations of CINDY2011/DYNAMO and HARIMAU2011. CINDY2011/DYNAMO and HARIMAU2011 were conducted over the Indian Ocean from October 2011 to January 2012 and Sumatra Island, Indonesia in December 2011. Both observation datasets covered the preconditioning stage of the MJO in December 2011. We found that convection was activated over the Sumatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Upper tropospheric moisture increases as large-scale subsidence is reduced in association with eastward circumnavigating dry planetary perturbations (Powell & Houze, 2015). Moisture variability can also be instigated by mixed Rossby-gravity waves (Muraleedharan et al, 2015) that may origin from the MC (Kubota et al, 2015) and Kelvin waves (DePasquale et al, 2014).…”
Section: Recent Results From In Situ Observationsmentioning
confidence: 99%
“…Upper tropospheric moisture increases as large-scale subsidence is reduced in association with eastward circumnavigating dry planetary perturbations (Powell & Houze, 2015). Moisture variability can also be instigated by mixed Rossby-gravity waves (Muraleedharan et al, 2015) that may origin from the MC (Kubota et al, 2015) and Kelvin waves (DePasquale et al, 2014).…”
Section: Recent Results From In Situ Observationsmentioning
confidence: 99%
“…The high-frequency variability in this study included any disturbances with periods shorter than approximately two weeks, such as convectively coupled equatorial waves (CCEWs), although they were not specified here. The role of CCEWs in the MJO in the statistical sense is still arguable (Kiladis et al 2009;Dias et al 2013), but some of the CINDY2011/DYNAMO studies suggested possible roles of CCEWs in the MJO initiation and development (Kubota et al 2015;Nasuno et al 2015;Kikuchi et al 2017b). Further investigations using multiple field data with increased density, together with high-resolution simulation data, are also intended in forthcoming studies.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, HARIMAU2006, 2007 and 2011 were in the westernmost area of the IMC (Propinsi Sumatera Barat or West Sumatra Province), targeting the MJOs from the Indian Ocean and their modification (Yoneyama et al 2008(Yoneyama et al , 2013Kamimera et al 2012;Kubota et al 2015, with the MISMO and CINDY projects), the diurnal cycles of the major and smaller islands Kamimera et al 2012), and convective cloud structure and vertical coupling (Fukao 2006;Mori et al 2011;Kawashima et al 2006Kawashima et al , 2011Sakurai et al 2009Sakurai et al , 2011, with the Coupling Processes in the Equatorial Atmosphere (CPEA) project). HARI-MAU2008 and 2009 were performed over Kalimantan Island ).…”
Section: Jepp−harimau and Satreps−mccoe Projectsmentioning
confidence: 99%